Vocational training quality for skilled workers of railway profile: state and problems of organization - Bondarenko, T.; Ageeva, O. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the current state of the development of monitoring in the field of vocational training of qualified workers. The directions of research in the field of monitoring of vocational education are analyzed, examples of the use of monitoring systems at different levels of the functioning of the system of vocational education are given. The authors outline the range of tasks that need to be addressed when developing and implementing the process of monitoring the quality of vocational training of qualified workers of the railway profile, taking into account the specifics of their training. The practical state of monitoring the development is considered at two levels: the external, which is oriented towards the social space of the educational institution and the market of educational services, and the internal one, which is aimed at researching and developing the educational environment of the educational institution. The example of complex monitoring of educational and industrial activity of vocational education establishments is given. It is based on the methodology of integrated monitoring of the quality of vocational education and training, according to the quantitative indicators of statistical, sociological and other types of research.